RELASIONALITAS TATA HIDUP BERNEGARA Pendalaman Perspektif Armada Riyanto Dari Para Peletak Dasar Filsafat Etika Politik - Antono Wahyudi (Litbang STFT Widya Sasana Malang, 2016)
In building and managing the order of life in a Nation, human being needs to own as well as to implement the ethics value. Ethics is neither a rule nor social norms that must be followed by human being. Instead, it is more emphasizing critically to the orientation of life so that he or she is free from the shackles of inauthentic consciousness. In addition, it must be realized that human being has the nature in building its relationality in order to accomplish the order of life. The implementation is started from the smallest group (family) which eventually will end up and gives full shape to the largest group (Nation). One of the most important components to bring out the relationality is to raise the awareness of the concept “I and Thou”, in which also simultaneously set in motion the virtues of friendship and dialogue. However, it is undeniable that human being also has a tendency to act arbitrarily. Therefore, it needs a collective agreement by habituating each individual to engage in dialogue and act fairly in order to build relationality for the sake of the order of life.